2019
DOI: 10.1038/s41598-019-41617-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic improvement in spring maize yield and quality with micro/nanobubbles water oxygation

Abstract: Soil oxygen shortages in root areas have negative effects on crop growth and decrease crops yield and quality, and soil hypoxia conditions will be aggravated by application of subsurface drip irrigation (SDI). A two-year field experiment was conducted to evaluate the response of maize to micro/nanobubbles oxygation (MNBO) at three dissolved oxygen (DO) concentrations (10, 20 and 30 mg/L) and seven MNBO periods (vegetative stage, reproductive stage, filling and ripening stage, combination of two stages and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The measurements of the particle size and concentration distribution of the MNBs produced under different cycle running times in this experiment are shown in Figure 9. The preparation of the MNBs using the dissolved gas release method can be divided into two processes: the pressurization to dissolve the gas and the decompression to release it [28]. According to the results, the sizes of the MNBs showed two peaks, with peak particle size ranges of 70-80 nm and 700-900 nm.…”
Section: Particle Size and Distribution Properties Of Co 2 Mnbs From ...mentioning
confidence: 99%
“…The measurements of the particle size and concentration distribution of the MNBs produced under different cycle running times in this experiment are shown in Figure 9. The preparation of the MNBs using the dissolved gas release method can be divided into two processes: the pressurization to dissolve the gas and the decompression to release it [28]. According to the results, the sizes of the MNBs showed two peaks, with peak particle size ranges of 70-80 nm and 700-900 nm.…”
Section: Particle Size and Distribution Properties Of Co 2 Mnbs From ...mentioning
confidence: 99%
“…Recently, nanobubbles (NBs) have attracted increasing attention in agriculture because of their intriguing characteristics such as high stability, enhanced gas solubility, and the generation of reactive oxygen species (ROS) . Irrigation with water containing NBs has proven effective to promote diverse seed germination, , plant growth, , and crop yield. Such promotion effects were repeatedly reported for different plants (e.g., tomato, cucumber, and maize) with different types of NBs such as oxygen (O 2 ), air, and nitrogen (N 2 ) in irrigation. ,,, However, the effect of the NBs on the plant promotion still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies primarily indicated that appropriate levels of ROS generated by NBs can serve as signal molecules and promote plant growth. ,,, For example, Liu et.al showed that both low concentrations of H 2 O 2 and the air NB water can stimulate the germination of barley seeds . NBs could produce exogenous hydroxyl radicals (·OH) that may directly regulate the expression of genes for peroxidase and promote cell proliferation and survival .…”
Section: Introductionmentioning
confidence: 99%
“…至此, 纳米气泡这一全新的研究领域逐步获得认可并得以快 速发展 [13][14][15][16][17] . , 基于扩散理论和Laplace 压强的Epstein-Plesset理论近乎完美地揭示了微米级 气泡在水中的演化行为并得到实验结果的支撑 [27] [31,32] 、土壤增氧 [33] 和农作物种植 (如玉米及水稻种植) [34,35] 等, 医学上也有脂质体包裹 纳米气泡增强超声成像的示例 [36] . 虽然已观察到(微) Scanning transmission X-ray microscopy (STXM), X-ray emission spectroscopy (including X-ray fluorescence (XRF), resonant soft X-ray emission) and small angle X-ray scattering (SAXS); (b) principles of X-ray absorption spectroscopy, X-ray resonant inelastic/elastic scattering and X-ray emission spectroscopy, E vac is the vacuum level, LUMO is the lowest unoccupied molecular orbital, HOMO is the highest occupied molecular orbital, the molecular orbital of water molecule is presented.…”
mentioning
confidence: 99%